Foot Massage as an Alternative to Improve Sleep Quality of Elderly Patients - Yeni Kartika Sari; Wimar Anugrah Romadhon; Tri Wahyuni; Meli Diana (STIKes Patria Husada Blitar, 2025)
A high proportion of elderly in Indonesia experienced poor sleep quality. The psychological impact of poor sleep quality is decreased cognitive function, decreased immunological function, and negative and more emotional changes in thoughts. Foot massage can induce deep relaxation, alleviate anxiety and pain, and enhance sleep quality. This research aimed to determine the impact of foot massage on the sleep quality of elderly patients. This was quantitative research, a type of pre-experimental research. The design used a group pre-test and post-test design. The number of respondents was 20 elderly patients with a composmentis who were treated in the inpatient ward of the Budi Rahayu Catholic Hospital and were taken using purposive sampling—data collection using PSQI questionnaires before and after foot massage. The research indicated that the average sleep quality score was 8.4 before the foot massage, and decreased to 4.85 after the massage. The Wilcoxon signed ranked massage test results obtained a p-value of 0.000. It can be concluded that there is a notable difference in sleep quality score before and after foot massage in elderly patients. Nurses are encourage to utilize foot massage as an independent intervention to enhance the sleep quality of elderly patients. Nurses can educate the patient’s family on foot massage techniques to enhance the quality of the patient’s sleep and help speed up the healing process.